BAHAN AJAR ENGLISH FOR ISLAMIC FASHION: PENGEMBANGAN MATERI ESP TINGKAT DASAR BERBASIS CANVA DAN WORDWALL - Azis Nurkholis Majid; Hanni Haernai; Dede Ananta K Perangin- Angin (LPPM Politeknik Pajajaran ICB, 2025)
The globalization of the fashion industry has expanded the need for English language competence, especially in professional and culturally nuanced contexts. Despite the growing demand for modest fashion globally, many professionals and students in this field still lack access to relevant English learning materials. The challenge is even more pronounced for Islamic fashion professionals in Indonesia, who require instructional resources that reflect both the technical demands of the industry and Islamic cultural values. This study aims to develop English for Specific Purposes (ESP) learning materials for Islamic fashion at the A1 level. Adopting a descriptive material development approach grounded in the ESP framework by Hutchinson and Waters (1987), the researcher designed five thematic units using Canva to deliver interactive, visually rich presentations. Wordwall was integrated as a complementary tool to support contextual vocabulary practice and self-paced learning. The materials focus on key topics such as fashion items, styles, materials, design elements, and fashion presentations. The development process demonstrates that visual-based and culturally responsive ESP materials can foster learner engagement and better support communication needs in Islamic fashion contexts. This study highlights the value of integrating technology-enhanced media in designing effective, relevant, and inclusive ESP resources for specific professional domains.